2017
DOI: 10.1016/j.ceramint.2017.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Raman analyses of Chinese huafalang and related porcelain wares. Searching for evidence for innovative pigment technologies

Abstract: Eighteen Chinese painted enamelled porcelains and three Chinese enamelled Yixing stonewares dated to the 16 th to 19 th centuries and kept at the Musée national des arts asiatiques-Guimet (MNAAG), have been analysed with a mobile Raman set-up to identify their enamelling technology. Different Grand Feu (leadless or lead-poor colourless and blue enamel) and Petit Feu (lead-rich red (hematite), yellow and green (Pb-Sn/Sb/X pyrochlore) and black enamels) glazes were respectively identified on wares from the wucai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 68 publications
7
108
1
2
Order By: Relevance
“…Complex multicoloured décors for potteries are made by using a succession of thin glaze layers (the thickness being close to 10–20 μm, i.e., larger than the z‐size of the focused spot obtained with ×50 or even ×100 microscope objective) and taking into account the broadening of the spot within the silicate glass. Figure compares the Raman spectra (as recorded, not expanded) collected on the same enamelled wucai porcelain with ×50 (Nikon) and ×200 (Mitutoyo) LWD objectives . The highest intensity of the Raman signature of both the crystalline (pigments) and amorphous (glaze matrix) phases recorded with a ×200 objective is obvious.…”
Section: Experimental and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex multicoloured décors for potteries are made by using a succession of thin glaze layers (the thickness being close to 10–20 μm, i.e., larger than the z‐size of the focused spot obtained with ×50 or even ×100 microscope objective) and taking into account the broadening of the spot within the silicate glass. Figure compares the Raman spectra (as recorded, not expanded) collected on the same enamelled wucai porcelain with ×50 (Nikon) and ×200 (Mitutoyo) LWD objectives . The highest intensity of the Raman signature of both the crystalline (pigments) and amorphous (glaze matrix) phases recorded with a ×200 objective is obvious.…”
Section: Experimental and Proceduresmentioning
confidence: 99%
“…Figure 3 compares the Raman spectra (as recorded, not expanded) collected on the same enamelled wucai porcelain with ×50 (Nikon) and ×200 (Mitutoyo) LWD objectives. [52,53] The highest intensity of the Raman signature of both the crystalline (pigments) and amorphous (glaze matrix) phases recorded with a ×200 objective is obvious.…”
Section: Choice Of the Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese enamelled precious artefacts [14] in addition to elemental composition measurements of some shards [15][16][17][18][19][20][21][22][23] showed that Chinese craftsmen used different types of cobalt sources including arsenicrich cobalt ores similar to those used in Europe for soft-paste porcelain [5,11] and Limoges enamels [24], and manganese-and/or iron-rich ores of Asian origins [16][17][18]25] to make blue decorations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that useful information can be obtained by non-invasive mobile techniques, based on portable XRF and Raman spectroscopies [14,[24][25][26][27][28][29]. The great advantages of Raman microspectroscopy are: i) its non-invasive character that allows studying very precious items, ii) the availability of high sensitivity mobile instruments that permit the measurements of many objects per day in exhibition, ancient tombs or storage rooms, iii) a great efficiency in the identification of many colouring agents, even at low concentration and iv) the possibility of very local and in-depth analysis.…”
Section: Introductionmentioning
confidence: 99%